ENTOMOPHAGY: ARE INSECTS SAFE FOR HUMAN FOOD? - M. A. Polubesova; M. V. Novikova (Zakharova); D. S. Ryabukhin (Пищевые системы, 2022)
Edible insects are a promising product for the Russian food market. This is due to their high nutritional value, the presence of essential amino acids, useful omega‑3 and omega‑6 polyunsaturated fatty acids. The balanced content of macro- and microelements in the composition of such a product allows us to talk about its potential benefits for human health. However, at present there is no reliable information about the attitude of Russian citizens to eating insects. The adult population has a more traditional view of nutrition, preferring proven types of food in their consumer basket. As a result of the study, it was found that women are 50% more likely to express concerns about the safety of edible insects compared to men and, in general, are more negatively disposed towards entomophagy (edible insects and products made from them). On the other hand, men are more likely to assume that the population is not ready to try insect foods because people are not sure of their safety. From the point of view of women, consumers are concerned about the lack of available scientific information on this topic and consider this issue to be insufficiently studied. Among all respondents, 80% answered that a TV report on the health benefits of edible insects would not change their attitude towards entomophagy. Moreover, 44% of respondents consider it inexpedient to open production facilities for edible insects in Russia. This judgment is consistent with their opinion about the low safety of food from insects. Women were twice as likely to respond negatively to the question about permitting the production of edible insects in Russia compared to men.